Analisis Pengaruh Layanan GoFood Terhadap Peningkatan Penjualan Pedagang Kaki Lima - Herna P.W. Hutabarat (Badan Penerbit STIEPARI Press, 2023)
This journal presents the results of an analysis of the influence of GoFood services on increasing sales of street vendors, by embracing various sources of information, including scientific articles, books, online data and the latest information. This research brings together data from various sources to detail the positive impact that the GoFood platform has on street vendors. Through a synthesis of this information, we found that GoFood significantly increased street vendor sales by expanding market access and providing adequate services for customers. Apart from that, the analysis also shows how street vendors who are smart in utilizing this technology tend to achieve greater profits. Thus, this journal illustrates the importance of technological adaptation in supporting the economic growth of street vendors in the current digital era.